Usability Test for User Centered Design-Based Industrial Internship Management System - Ratih Hafsarah Maharrani; Abdul Rohman Supriyono; Lutfi Syafirullah; Riyadi Purwanto (Universitas Negeri Padang, 2022)
Internship is one of the efforts to align the knowledge or competencies obtained during the lecture with the world of work directly. In this research will be built an industrial internship management system starting from industry submissions, internship guidance and assessment of industry seminars with User Centered Design. This UCD method focuses on designing user-oriented systems. The results of the study were conducted with a usability test with 20 items (items) and 19 respondents, it can be concluded that each component of usability gets a value of > 80% which means it has a very good predicate, while the overall usability test of 87.69% includes a very good predicate.